Alienation in the Urban Form of the Port Cities (Ashar City) as a Model - Baqer, Khalid Sameer; Joboury, Nisreen Razaq Ibraheem (Basrah Journal for Engineering Sciences, 2023)
Alienation is a broad concept, conveying a bunch of cognitive issues, such as Language, Philosophy, Sociology, and Psychology in addition to Architecture as well. Society is affected by a group of factors, reflected by various phenomena giving rise to making a change in society in all different aspects. There exist various concepts, such as estrangement, weirdness, and place, which must be distinguished from alienation in all its forms and categories. These are spatial alienation, social alienation, and psychological alienation. In this respect, spatial alienation means the break of continuity of Man from the place he/she belongs to due to the defragmentation in the urban fabric it can affect its architectural components. In addition, it created some sort of discrepancy and mess between the physical components of the city and its worn-out urban voids. Consequently, this creates a weakness in the social and functional interaction, as well as a divergence of the urban landscape of the urban fabric of the port cities from the cultural and civilized legacy and the identity of the place as well. This research entails concepts relating to alienation, study, and analysis of the urban form of the port cities. AL-Ashar city has been chosen to be the model of the study sample. The research has come to findings that there exists alienation between urban voids and the physical elements within the urban fabric leading to weakness in the continuity and affiliation to the identity of the place and the city’s architectural heritage. Thus, the research includes two axes: first, the theoretical concepts, while the second is the field study followed by a descriptive approach, then we introduce the outcomes, the most important conclusions, and recommendations.